2020
DOI: 10.1111/pce.13759
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves rice salinity stress tolerance by NADPH oxidase‐dependent control of the plasma membrane K+ transporters and K+ homeostasis

Abstract: This study aimed to reveal the mechanistic basis of the melatonin-mediated amelioration of salinity stress in plants. Electrophysiological experiments revealed that melatonin decreased salt-induced K + efflux (a critical determinant of plant salt tolerance) in a dose-and time-dependent manner and reduced sensitivity of the plasma membrane K +-permeable channels to hydroxyl radicals. These beneficial effects of melatonin were abolished by NADPH oxidase blocker DPI. Transcriptome analyses revealed that melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 107 publications
8
73
0
Order By: Relevance
“…Subsequent pharmacological evidence confirmed that sodium orthovanadate or amiloride significantly blocked both Na + effluxes and H + influxes in NaCl‐stressed CrHYD1 roots, and contrasting changes were found in K + effluxes (Figure 5). Similar to the previous reports (Liu et al, 2020; Sun et al, 2008; J. Zhang et al, 2016), above results indicated that MT‐dependent Na + extrusion (Figures 3a and 4a) in CrHYD1 transgenic lines was partly the result of an active Na + /H + antiport across the plasma membrane (Chen et al, 2007). Combined with the results in Figures 3 and 4, our findings provided evidence that endogenous H 2 regulated MT‐dependent positive ion transport, possibly explaining why CrHYD1 transgenic plants have greater tolerance to salt stress.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Subsequent pharmacological evidence confirmed that sodium orthovanadate or amiloride significantly blocked both Na + effluxes and H + influxes in NaCl‐stressed CrHYD1 roots, and contrasting changes were found in K + effluxes (Figure 5). Similar to the previous reports (Liu et al, 2020; Sun et al, 2008; J. Zhang et al, 2016), above results indicated that MT‐dependent Na + extrusion (Figures 3a and 4a) in CrHYD1 transgenic lines was partly the result of an active Na + /H + antiport across the plasma membrane (Chen et al, 2007). Combined with the results in Figures 3 and 4, our findings provided evidence that endogenous H 2 regulated MT‐dependent positive ion transport, possibly explaining why CrHYD1 transgenic plants have greater tolerance to salt stress.…”
Section: Discussionsupporting
confidence: 91%
“…The data above were consistent with the results in Figure 3. Similar changes for ion fluxes in salt‐resistant plants were also reported (Liu et al, 2020; Sun et al, 2008; J. Zhang et al, 2016). Subsequent pharmacological evidence confirmed that sodium orthovanadate or amiloride significantly blocked both Na + effluxes and H + influxes in NaCl‐stressed CrHYD1 roots, and contrasting changes were found in K + effluxes (Figure 5).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations